(untitled) - Anderson, Alun M. (Harlow, Essex, UK, 1984)
This edition provides comprehemsive coverage of the science and technology system in Japan. The book combines information on official and corporate bodies with analysis and interpretation, and covers both structures and institutions of research. Special emphasis is laid on industrial research, particularly in the private sector.
Keywords: Science,Science and state,Technology and state,Khoa học,Nhà nước và khoa học,Nhà nước và công nghệ; Japan,Japan,Japan,Nhật Bản,Nhật Bản,Nhật Bản